Gallbladder polyp: A rare lesion in pediatric population - Amit Ray (Journal of Indian Association of Pediatric Surgeons, 2013)
An 11-years-old girl with a polyp in the gallbladder is reported. Laparoscopic cholecystectomy was curative.